Ideology in Biology: Theism Meets Atheism in the Case of Abiogenesis - Ruffinengo, Marc (The journal of religion & society, 2021)
Abiogenesis is the proposed process through which inanimate matter eventually led to life on earth. As a research area, the issue is certainly loaded with fodder for debate and philosophical and ideological disagreement about what life is and how it came to be. Dealing with the origin of life (OoL) obviously has the potential to tread into spiritual and religious grounds for both scientists interested in this area but also for the public at large when any debate about "where did we come from?" arises. However, it is not just the general public that struggles with balancing religious and spiritual explanations for how people came into being with scientific evidence. As we will show, there is a lively debate among OoL researchers about a similar set of scientific facts pointing to the intervention of a transcendent designer or such an idea being incompatible with science generally. Furthermore, we note that much of this debate is centered around the concepts of ontological and methodological materialism. While we make no claims about resolving or contributing meaningfully to the debate it is worth pointing out, especially to outside observers, that such a debate is in fact alive and well among OoL researchers. Thus, it is certainly possible for OoL researchers to view abiogenesis as an atheistic endeavor and many do. However, atheism is not a requirement to believe that abiogenesis played a role in the OoL as many scientists view such discoveries as a "mark of the Creator" as opposed to merely an idea that life must have come from inanimate matter.